Kontribusi Self-Esteem Terhadap Prestasi Mahasiswa Pada Universitas Di Kabupaten Badung - Arie Suarthana, I Nyoman Henry; Dewi, Tiara Kusuma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
One of the causes of the decline in learning achievement obtained by students is self-esteem so that in this case students have a tendency to find it difficult to be appreciated or accepted, this study aims to analyze the contribution of self-esteem to student achievement in the Management S1 study program at universities in Badung Regency. , this research is a quantitative research with sampling technique using purposive sampling method, and the hypothesis is analyzed using single regression analysis. Based on the results of data analysis shows that the Self-esteem variable is able to predict the learning achievement of students of the Management S1 Study Program. Self-esteem has a positive effect on student learning achievement, the higher the level of self-esteem, the higher the student's learning achievement.